2016
DOI: 10.18632/oncotarget.11861
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of miR-381 is a favorite prognosis factor and enhances the chemosensitivity of osteosarcoma

Abstract: Osteosarcoma (OS) is the most common primary bone malignancy with a poor prognosis for all races and both sexes. In this study, we found that miR-381 is a positive prognosis factor for OS patients that OS patients with a low expression of miR-381 had a longer survival time after surgical intervention, and miR-381 expression promotes MG-63 cell proliferation and cell invasion ability. Our results also showed a strong negative correlation between the expression of miR-381 and LRRC4 (brain relative specific expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…It is reported that miR-93 can repress apoptosis after cerebral ischemia via interleukin-1 [38]. Similarly, a previous study proved that miR-381 was overexpressed in the mature brain and normal hippocampal neurons [13], and decreasing miR-381 expression inhibited cell proliferation and invasion [39, 40], from which we inferred that up-regulation of miR-381 inhibited neuronal apoptosis.…”
Section: Discussionsupporting
confidence: 62%
“…It is reported that miR-93 can repress apoptosis after cerebral ischemia via interleukin-1 [38]. Similarly, a previous study proved that miR-381 was overexpressed in the mature brain and normal hippocampal neurons [13], and decreasing miR-381 expression inhibited cell proliferation and invasion [39, 40], from which we inferred that up-regulation of miR-381 inhibited neuronal apoptosis.…”
Section: Discussionsupporting
confidence: 62%
“…Our results indicated that miR-381 was down-regulated in DDPresistant breast cancer tissues and cells, and miR-381 overexpression could overcome DDP resistance in DDPresistant breast cancer cells (MCF-7/DDP and MDA-MB-231/DDP). Ã P < 0.05. et al, 2013a; Wang et al, 2015;Li et al, 2016). Collectively, our data demonstrated that miR-381 could facilitate the sensitivity of breast cancers to DDP.…”
Section: Discussionsupporting
confidence: 56%
“…4 There is considerable evidence suggesting that miR-381 functions as a suppressor in cancer proliferation, migration, and invasion. 5 For example, miR-381-inhibited pituitary tumor cell tumorigenesis by targeting PTTG1. 6 However, in other studies, miR-381 was validated to promote glioma cell proliferation and pituitary tumor growth in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%